Arab's Research Productivity and Contribution to Vascular and Interventional Radiology Literature - Yousof Al Zahrani; Mohammad Arabi (The Arab Journal of Interventional Radiology)
Objective: Vascular and interventional radiology (VIR) is one of the most rapidly growing fields of medicine. In this report, we evaluate the contribution of Arab countries to VIR publications and literature. Materials and Methods: Using PubMed database, we reviewed the total number of VIR publications from all Arab countries. In addition, we evaluated the total number of IR articles from each individual country, number of publications in VIR specialty journals and the type of manuscripts. Results: Seventy-four articles from different Arab countries were published in different journals from 1988 to 2016. Only 11 (14.9') articles were published in interventional radiology journals. The majority of these publications were from Kingdom of Saudi Arabia 31 (41.9') articles, followed by 20 (27.02') articles from Egypt, 7 articles (9.5') from Jordan, 6 articles (8.1) from Kuwait, and 4 articles (5.4') from Morocco. There was one article (1.4') from Lebanon, United Arab Emirates, Oman, Tunis, and Qatar. Nine (12.2') articles from different Arab countries were published in the two highest impact specialty journals in VIR. Conclusion: This review demonstrated the limited number of publications and poor contribution of Arab countries to VIR literature. Collaborative efforts of researchers, governments, and funding bodies are needed to improve research output in this important field of medicine.